Metagenomic analysis of the camel rumen archaeome and its functional potential - Abdelmegeid, Mohamed; Zeineldin, Mohamed; Seboussi, Rabiha; Mohamadin, Mahmoud; Alharthi, Abdulrahman S.; Mansour, Nabil; Okasha, Lamiaa A.; Elolimy, Ahmed A.; Saliu, Eva-Maria (Frontiers in Veterinary Science, 2026)
The camel rumen harbors a unique and underexplored archaeal community that plays a critical role in methanogenesis and ruminal fermentation. This study aimed to characterize the taxonomic composition and functional potential of the camel rumen archaeome using whole-genome shotgun metagenomic sequencing. Across the seven healthy racing camel rumen samples, the archaeal community was dominated by Euryarchaeota (50.1 ± 0.02%) and the Methanomada group (49.7 ± 0.03%), with Methanobacteriaceae and Methanobrevibacter representing the predominant family and genus, respectively. Species-level analysis revealed Methanobrevibacter sp. YE315 and Methanobrevibacter millerae as the most abundant archaeal species across all samples. Alpha-diversity analyses indicated a diverse and evenly distributed archaeal population in the camel rumen. Beta-diversity based on Bray–Curtis and Jaccard dissimilarities demonstrated strong similarity among samples, highlighting a conserved archaeal community structure across individuals. Core microbiome assessment (≥ 80% occurrence) identified seven dominant Methanobrevibacter species as the stable core archaeome. Functional profiling revealed a consistent metabolic repertoire dominated by methanogenesis (PWY-5209), amino acid biosynthesis, and nucleotide metabolism pathways. Functional alpha-diversity metrics and beta-diversity clustering highlighted low inter-sample variability and a stable functional architecture. Overall, the camel rumen archaeome exhibited a stable and conserved community composition and functional architecture, underscoring its central role in hydrogen utilization and methane production within the rumen ecosystem. Although based on a small number of animals from a single location and therefore descriptive in nature, this study provides a comprehensive metagenomic overview of the taxonomic and functional profiles of the camel rumen archaeal community.